2011
DOI: 10.1016/j.jss.2010.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Selection of third party software in Off-The-Shelf-based software development—An interview study with industrial practitioners

Abstract: The success of software development using third party components highly depends on the ability to select a suitable component for the intended application. The evidence shows that there is limited knowledge about current industrial OTS selection practices. As a result, there is often a gap between theory and practice, and the proposed methods for supporting selection are rarely adopted in the industrial practice. This paper's goal is to investigate the actual industrial practice of component selection in order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(65 citation statements)
references
References 42 publications
5
60
0
Order By: Relevance
“…Component selection process: none of the interviewees reported the usage of formal evaluation processes, which are abundant in literature [7,10], in their projects. This observation is similar to findings from a previous study [20]. The evaluation activity is normally undertaken in ad hoc manner.…”
Section: Requirements Elicitation Practices Source Of Requirementssupporting
confidence: 91%
“…Component selection process: none of the interviewees reported the usage of formal evaluation processes, which are abundant in literature [7,10], in their projects. This observation is similar to findings from a previous study [20]. The evaluation activity is normally undertaken in ad hoc manner.…”
Section: Requirements Elicitation Practices Source Of Requirementssupporting
confidence: 91%
“…Furthermore, the literature has pointed out the underestimation of integration effort and inefficient debugging as problematic areas that require further investigation [20]; therefore, we stated RQ1.2 and RQ1.3 respectively. Finally, as a previous study [13] reported that getting OSS components information seems to become a continuous monitoring activity rather than being on a project demand basis, we stated RQ1.4 to understand how integrators monitor OSS communities.…”
Section: Survey On Oss Integration Issues and Community Supportmentioning
confidence: 75%
“…The interview guide was carefully designed following the guidelines stated in [11] and previous experience performing international surveys from several members of the team [12], [13], [14, [15]. The survey was designed as a 5-section survey, with both closed and open questions.…”
Section: Methodsmentioning
confidence: 99%
“…The interview guide used in the study may be consulted at [5]. The target population was practitioners in charge of performing OSS component selection activities.…”
Section: Empirical Study In Selection Of Oss Componentsmentioning
confidence: 99%